Blending Online Asynchronous and Synchronous Learning - Yamagata-Lynch, Lisa C. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2014)
In this article I will share a qualitative self-study about a 15-week blended 100% online graduate level course facilitated through synchronous meetings on Blackboard Collaborate and asynchronous discussions on Blackboard. I taught the course at the University of Tennessee (UT) during the spring 2012 semester and the course topic was online learning environments. The primary research question of this study was: How can the designer/instructor optimize learning experiences for students who are studying about online learning environments in a blended online course relying on both synchronous and asynchronous technologies? I relied on student reflections of course activities during the beginning, middle, and the end of the semester as the primary data source to obtain their insights regarding course experiences. Through the experiences involved in designing and teaching the course and engaging in this study I found that there is room in the instructional technology research community to address strategies for facilitating online synchronous learning that complement asynchronous learning. Synchronous online whole class meetings and well-structured small group meetings can help students feel a stronger sense of connection to their peers and instructor and stay engaged with course activities. In order to provide meaningful learning spaces in synchronous learning environments, the instructor/designer needs to balance the tension between embracing the flexibility that the online space affords to users and designing deliberate structures that will help them take advantage of the flexible space.